SGIP1 in axons prevents internalization of desensitized CB1R and modifies its function - Durydivka, Oleh; Mackie, Ken; Blahos, Jaroslav (Frontiers in Neuroscience, 2023)
In the central nervous system (CNS), cannabinoid receptor 1 (CB1R) is preferentially expressed in axons where it has a unique property, namely resistance to agonist-driven endocytosis. This review aims to summarize what we know about molecular mechanisms of CB1R cell surface stability in axonal compartments, how these impact CB1R signaling, and to consider their physiological consequences. This review then focuses on a potential candidate for maintaining axonal CB1R at the cell surface, Src homology 3-domain growth factor receptor-bound 2-like endophilin interacting protein 1 (SGIP1). SGIP1 may contribute to the polarized distribution of CB1R and modify its signaling in axons. In addition, deletion of SGIP1 results in discrete behavioral changes in modalities controlled by the endocannabinoid system in vivo. Several drugs acting directly via CB1R have important therapeutic potential, however their adverse effects limit their clinical use. Future studies might reveal chemical approaches to target the SGIP1-CB1R interaction, with the aim to exploit the endocannabinoid system pharmaceutically in a discrete way, with minimized undesired consequences.